Adsorption mechanisms of chromate and phosphate on hydrotalcite: A combination of macroscopic and spectroscopic studies. (April 2019) - Hsu, Liang-Ching; Tzou, Yu-Min; Chiang, Po-Neng; Fu, Wei-Min; Wang, Ming-Kuang; Teah, Heng Yi; Liu, Yu-Ting
Abstract: Hydrotalcite (HT) is a layered double hydroxide (LDH), which is considered as a potential adsorbent to remove anion contaminants. In this study, adsorption of chromate (CrO4 ) and phosphate (PO4 ) on HT was conducted at various pH and temperatures. Related adsorption mechanisms were determined via the isotherm, kinetic, and competitive adsorption studies as well as the Cr K -edge X-ray absorption fine-structure (XAFS) spectroscopy. The maximum adsorption capacities for CrO4 and PO4 on HT were 0.16 and 0.23 mmol g −1 . Regarding adsorption kinetics, CrO4 and PO4 adsorption on HT could be well described by the second order model, and the rate coefficient of CrO4 and PO4 on HT decreased significantly with the increasing pH from 5 to 9. The adsorption kinetics for CrO4 and PO4 were divided into fast and slow stages with the boundary at 15 min. This biphasic adsorption behavior might be partially attributed to multiple reactive pathways including anion exchange and surface complexation. Fitting results of Cr K -edge EXAFS analysis showed a direct bonding between CrO4 and Al on HT surfaces. Such a surface complexation appeared to be the rate-limiting step for CrO4 adsorption on HT. By contrast, the diffusion through the hydrated interlayer space of HT was the major rate-limiting step for PO4 . This study determined the adsorption behaviors of CrO4 and PO4 on HT, including the initial transfer process and the subsequent adsorption mechanisms. Such information could improve the strategy to use HT as the potential adsorbent for the remediation of anionic pollutants. Graphical abstract: Image 1 Highlights: Adsorption capacity of PO4 on HT is greater than that of CrO4 . Adsorption kinetics of CrO4 and PO4 on HT are well described by 2nd order model. Cr K-edge EXAFS data showed a direct bonding between Cr and Al on HT surfaces. Surface complexation is the rate-limiting step for CrO4 adsorption on HT. Diffusion through the interlayer of HT is the major rate-limiting step for PO4 . Abstract : This research demonstrated HT is a potential adsorbent for recovering toxic anions and provided a significant understanding in the interaction of CrO4 and PO4 with HT.